2015
DOI: 10.1149/2.0061506jss
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Etching at the Tipping Point: An Overview

Abstract: The ability to achieve near-atomic precision in etching different materials when transferring lithographically defined templates is a requirement of increasing importance for nanoscale structure fabrication in the semiconductor and related industries. The use of ultra-thin gate dielectrics, ultra thin channels, and sub-20 nm film thicknesses in field effect transistors and other devices requires near-atomic scale etching control and selectivity. There is an emerging consensus that as critical dimensions approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
162
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(180 citation statements)
references
References 139 publications
2
162
0
Order By: Relevance
“…Much attention is focused on atomic-scale (i.e. sub-nanometer-scale) control of surface reactions for materials processing [5,48,49]. As the dimensions of semiconductor devices continue to diminish, thin film deposition and etching techniques often demand control at atomistic length scales.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Much attention is focused on atomic-scale (i.e. sub-nanometer-scale) control of surface reactions for materials processing [5,48,49]. As the dimensions of semiconductor devices continue to diminish, thin film deposition and etching techniques often demand control at atomistic length scales.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…The technological requirements to maintain atomistic control in PMI and minimize the damage of materials while changing the material/structure in a desirable fashion have pushed plasma-based techniques increasingly towards fundamental limits [5]. For example, plasmas with a low ion energy have been used for plasma-assisted atomic layer deposition (ALD) [48] and atomic layer etching (ALE) [49]. Material surface processing for biomedical applications has also attracted much attention.…”
Section: Acknowledgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be a single atomic (or molecular, as in this work) layer etched in one etch cycle. [6][7][8] Historically, ALE was developed mostly using ion beam or neutral beam etching systems, 5 often custom built. Recently, it was suggested that conventional plasma etch tools can be used for ALE (Ref.…”
mentioning
confidence: 99%